Fechamento de subtópicos em diálogos assimétricos (Revista de Estudos da Linguagem, 1997)
AbstractThis essay classifies sub-topic closing in two categories: the phrastic, in which the discurse sections are developed in a linear manner, in contrast with the paraphrastic, in which the rhetorical closing recycles the previous information. The data are then subjected to a computational programme which selects factors, which determine the same paraphrastic closing: (–) world knowledge; (+) argumentation; (+) subjectivity; (+) basic sentence; (+) the female sex.